Terörizmin propagandası suçu - Yavuz, Muhammet İsmet (My University, 2023)
Terörizm, özellikle son yıllarda artan bir şekilde tüm dünyayı etkileyen olumsuz bir olgudur. Terörizme konu terör eylemleriyle ulaşılmak istenen amaçlardan birisi de korku ortamının oluşturulmasıdır. Söz konusu ortam yalnızca terörizme konu terör eylemleriyle değil, aynı zamanda bu eylemlerin propagandalarının yapılması suretiyle de oluşturulabilmektedir. Hatta terörizmin amaçlarından birinin propaganda olduğu da kabul edilmektedir. Yıkıcı terör eylemleriyle birlikte bu eylemlerin propagandasının yapılmasının aynı amaçlara hizmet ettiği düşünüldüğünde, terörizmin propagandasıyla mücadelenin de en az terörizmin kendisiyle mücadele etmek kadar hayati olduğu ortaya çıkmaktadır. Çalışmanın birinci bölümünde terörizm ve propagandaya ilişkin tanım denemelerine, kavramların özelliklerine yer verilmiş ve ilişkili kavramlardan farkları ortaya konmaya çalışılmıştır. İkinci bölümde ise 3713 sayılı Terörle Mücadele Kanunu’nun 7. maddesinin 2. fıkrasında düzenlenen terörizmin propagandası suçunun Türk hukuku içerisindeki gelişimi, suçun benzer suçlardan farkları incelenmiş, suçun maddi, manevi ve hukuka aykırılık unsurları ile kusurluluk bahsi ve suçun özel görünüş biçimlerine yer verilmiş, yaptırım, görevli mahkeme, muhakeme usulleri, zamanaşımı ve infaz usulleri açıklanmıştır.

Terrorism is a negative phenomenon that has been affecting the whole world, especially in recent years. One of the aims of terrorism is to create a climate of fear. This atmosphere can be created not only through terrorist acts but also through propaganda. In fact, it is recognized that propaganda is one of the goals of terrorism. Considering that the propaganda of terrorist acts serves the same goals as destructive terrorist acts, it becomes clear that combating terrorism propaganda is just as crucial as combating terrorism itself. In the first section of the study, attempts were made to define the concepts of terrorism and propaganda, examine the characteristics of the concepts, and distinguish them from related concepts by classification. In the second section, the development of the crime of propaganda of terrorism, regulated in the second paragraph of Article 7 of Law No. 3713 on the Fight Against Terrorism within Turkish law, was examined along with the differences of the crime from similar crimes. The material, spiritual, and unlawful elements of the crime, as well as the issue of fault and special forms of the crime were discussed, and the sanctions, competent court, trial provisions, statute of limitations, and enforcement provisions were explained.
The crime of propaganda of terrorism
Keywords: Law and legislation; Propaganda; Propaganda of terrorism; Terorism; Terörizm; Terörizmin propagandası; Terrorism; Yasa ve yasama